Sazonalidade e voltinismo do gafanhoto gigante, distribuição e infestação de tripes em cajueiro-anão - Maciel, Gabriela Priscila de Sousa (2021)
Cashew culture is an activity of high socioeconomic importance for the northeast region, however, the cashew tree (Anacardium occidentale L.) has been harmed by several pest insects, among which Tropidacris collaris (Stoll, 1813) stand out, which causes damage by feeding on leaves and Holopothrips fulvus Morgan, 1929 which feeds on various plant organs. The objective of the present study was to evaluate: a) the voltinism of T. collaris in dwarf cashew trees, b) the effects of climatic variables (solar radiation, maximum temperature, minimum temperature, average temperature, relative humidity, wind speed and reference evapotranspiration) on the population dynamics of T. collaris, c) the population dynamics of T. collaris in relation to the phenological stages of dwarf cashew, d) the seasonality of H. fulvus and the influence of abiotic variables (solar radiation, temperature, relative humidity, wind speed and rainfall) and biotics (mites of the family Phytoseiidae) on their population dynamics, e) the vertical distribution patterns of H. fulvus in the dwarf cashew plant and f) the susceptibility of genotypes of dwarf cashew tree to H. fulvus infestation under field conditions. The studies were conducted in an experimental area of cashew trees belonging to Embrapa in Pacajus/CE. The variations observed in the age structure of the T. collaris population demonstrated that this species is univoltine. Wind speed, evapotranspiration and relative humidity were significantly correlated with the population of T. collaris nymphs. The phenological stages of the leaf fall/leaf flow dwarf cashew tree provided the predominance of nymphs. As for the species H. fulvus, the highest population peaks were recorded between the months of October and December 2019, 49% of the fluctuation of insects was explained by the climatic factor of solar radiation. The phytoseiid mites found belong to the species Amblyseius aerialis (Muma, 1955), Iphiseiodes zuluagai (Denmark & Muma, 1972), Amblyseius largoensis (Muma, 1955) and Amblyseius tamatavensis Blommers, 1974. Among these, I. zuluagai was the species with the higher percentage of individuals. The percentage of leaves infested by H. fulvus and the average number of thrips per leaf were higher in the middle and basal strata of the plant, compared to the apical stratum. Furthermore, the cashew genotypes CAP 143/7, CAP 155, CAP 106/1, CAP 115/5, CAP 805/4 and BRS 226 were less infested by H. fulvus, while the CCP 76 genotype was the most infested.